2010
DOI: 10.1007/978-3-642-11250-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fingerprints of Solar and Stellar Oscillations

Abstract: Waves connect all the layers of the Sun, from its interior to the upper atmosphere. It is becoming clear now the important role of magnetic field on the wave propagation. Magnetic field modifies propagation speed of waves, thus affecting the conclusions of helioseismological studies. It can change the direction of the wave propagation, help channeling them straight up to the corona, extending the dynamic and magnetic couplings between all the layers. Modern instruments provide measurements of complex patterns … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Below we provide an overview of the recent advances in the field of multifluid modeling of the solar atmosphere. Previous reviews of the subject can be found in [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Below we provide an overview of the recent advances in the field of multifluid modeling of the solar atmosphere. Previous reviews of the subject can be found in [13][14][15].…”
Section: Introductionmentioning
confidence: 99%